2022
DOI: 10.3390/cells11172658
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Interactions during Early Drosophila Oogenesis: An Ultrastructural Analysis

Abstract: Drosophila oogenesis requires the subsequent growth of distinct egg chambers each containing a group of sixteen germline cells surrounded by a simple epithelium of follicle cells. The oocyte occupies a posterior position within the germ cells, thus giving a distinct asymmetry to the egg chamber. Although this disposition is critical for the formation of the anterior–posterior axis of the embryo, the interplay between somatic and germ cells during the early stages of oogenesis remains an open question. We uncov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Tight membrane attachment was also observed in NC-NC boundaries and FC-FC boundaries throughout the stages (Figure 1F, G). At all stages analyzed, we observed adherens junctions between FCs (Figure 1G, asterisk) as reported previously [36,37], and unique membrane processes between oocytes and NCs or between oocytes and FCs (Figure 1H, I) as reported recently [22].…”
Section: Ultrastructural Characterization Of Germline-soma Interactio...supporting
confidence: 89%
See 1 more Smart Citation
“…Tight membrane attachment was also observed in NC-NC boundaries and FC-FC boundaries throughout the stages (Figure 1F, G). At all stages analyzed, we observed adherens junctions between FCs (Figure 1G, asterisk) as reported previously [36,37], and unique membrane processes between oocytes and NCs or between oocytes and FCs (Figure 1H, I) as reported recently [22].…”
Section: Ultrastructural Characterization Of Germline-soma Interactio...supporting
confidence: 89%
“…However, it is unclear whether E-Cadherin is involved in interactions between these cell types. In early ultrastructural studies, no clear junction is identified in these cell types [1][2][3]22]. E-Cadherin has been also found to localize outside of the junction, known as non-junctional Cadherin [23][24][25][26][27], suggesting that E-Cadherin may also play a role without forming junctions.…”
Section: Introductionmentioning
confidence: 99%
“…For several years, it was thought the Drosophila oocyte lacked active centrosomes at stages where nuclear migration occurred, as suggested by the failure to detect them during early oocyte development [49] and by the fact that the meiotic spindle formed in the absence of centrosomes at the end of oogenesis [50]. More recently, several studies have documented the existence of active centrosomes during oocyte development [16,18,24,51]. As mentioned above, the oocyte contains at least 16 centrosomes that come together to form a cluster.…”
Section: Centrosome Involvementmentioning
confidence: 99%
“…Alternatively, if the M1 contractile ring constricts less than contractile rings formed in subsequent divisions, perhaps it must be reinforced by the recruitment of more actin filaments or stabilized by additional cell-cell junctions, which may impact growth. Extensive cell-cell contacts have been observed in the developing germ cell cysts (Loyer et al, 2015;Riparbelli et al, 2022;Tilney et al, 1996), but a comparison of their distribution within different regions of the germ cell cluster has not been performed. One final explanation we considered is that the growth of a posterior ring canal could depend on how many other ring canals exist within that germ cell.…”
Section: Ring Canal Scalingmentioning
confidence: 99%